TRANSPARENCY MODERATION IN SIPD TOWARDS GOVERNMENT PERFORMANCE IN MEDAN PETISAH DISTRICT - Sitompul, Gloria Natasia; Vadhila, Ananda; Alfarizi, M Rafa; Putri, Claudia Nazmal; Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Government performance plays a crucial role in achieving effective, efficient, and accountable governance. Its implementation still faces various administrative challenges, particularly those related to the utilization of the Regional Government Information System (SIPD) and the level of public information transparency. The quality of local government management is improved through data integration, accountability, and information transparency, designed as strategic instruments within the SIPD. Medan Petisah District has not yet had a significant and optimal impact on improving financial performance. This conceptual article aims to evaluate the role of transparency as a moderating variable and the relationship between SIPD implementation and government performance in Medan Petisah District. The issues evaluated include limited capacity in operating the SIPD, its implications for government performance, and the low level of public information transparency. The method used is a conceptual approach through literature studies on theories, various previous research results, and relevant government and regulatory information, transparency, and public sector performance. The expected results of this article are that transparency is able to moderate and strengthen the influence of the implementation of SIPD on improving the performance of the District Government which is compiled in a conceptual framework, and optimal transparency is expected to encourage the effective use of SIPD so that it has an impact on efficiency, accountability, and quality of public services in Medan Petisah District